2021
DOI: 10.1111/fwb.13718
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological controls on oviposition habitat are associated with egg‐laying phenology of some caddisflies

Abstract: Seasonal variation in resource availability can have strong effects on life histories and population densities. Emergent rocks (ERs) are an essential oviposition resource for multiple species of stream insects. The availability of ERs depends upon water depth and clast size, which vary with discharge and river geomorphology, respectively. Recruitment success for populations may depend on whether peak egg‐laying periods occur at times when ERs are also abundant. For multiple species that oviposit on ERs, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 48 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, a third metric developed by Lang et al (2017) of egg mass aggregation on individual rocks indicated that, despite there being more rocks and more rock surface area in restored‐treated and reference streams, females still selected a few specific protruding rocks. Previous studies reported higher aggregations of egg masses with lower abundance of protruding rocks (Lancaster et al, 2021), but it is common for stream insects to aggregate their eggs on a small proportion of the available egg‐laying habitat (e.g., Encalada, 2005; Lancaster & Downes, 2010; Peckarsky et al, 2000). The 106% higher aggregation of egg masses in restored‐treated versus restored‐untreated streams is evidence that the addition of protruding rocks increased the availability of egg‐laying habitat preferred by females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a third metric developed by Lang et al (2017) of egg mass aggregation on individual rocks indicated that, despite there being more rocks and more rock surface area in restored‐treated and reference streams, females still selected a few specific protruding rocks. Previous studies reported higher aggregations of egg masses with lower abundance of protruding rocks (Lancaster et al, 2021), but it is common for stream insects to aggregate their eggs on a small proportion of the available egg‐laying habitat (e.g., Encalada, 2005; Lancaster & Downes, 2010; Peckarsky et al, 2000). The 106% higher aggregation of egg masses in restored‐treated versus restored‐untreated streams is evidence that the addition of protruding rocks increased the availability of egg‐laying habitat preferred by females.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely these eggs all hatched, and there were no residual egg chorions visible on the rocks from hatched eggs; hence, this movement likely resulted in egg mortality. We posited that increasing egg‐laying habitat would cause egg masses to be distributed over more rocks (Lancaster et al, 2021), which might reduce egg mortality by decreasing the probability that if any one protruding rock was disturbed, it would not contain a large proportion of egg masses. The prevalence and aggregation results discussed above suggest that the extent to which this could be realized is low for highly selective females that aggregate their eggs on specific habitats, and it would depend strongly on the added egg‐laying habitat being preferred by females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While average water levels vary predictably with discharge, relationships between water level and ER number may not be straightforward across a full range of discharges (Jordt & Taylor, 2021;Miller et al, 2020). Lancaster et al (2021) compared water levels and ER densities across 2 years in three unregulated rivers. Emergent rock densities were consistently low at the highest water levels but were variable at low water levels, due to differences in local bed topography among sites.…”
Section: Introductionmentioning
confidence: 99%